Performing Glinka's opera A Life for the Tsar on the village stage - Mannherz, J (Cambridge University Press, 2021)
Between 1896 and 1917, the Perm΄ “Guardianship of Popular Sobriety”—an organization funded by the Ministry of Finance and supervised by the provincial governor—ran a popular choir program that engendered enthusiastic artistic collaboration between peasants, workers, the regional intelligentsia, and state officials. One major achievement of participants were amateur performances of Glinka's monarchical opera A Life for the Tsar throughout Perm΄ province. This article focuses on the musical activities of one peasant women, E.N. Shniukova, and argues that provincial and otherwise unknown musicians, many of whom were women, played a key role in spreading cultural values and shaping musical life in the early twentieth century. These regional musicians rejected the peripheral position that their location and social position otherwise suggested and proudly viewed their villages as centers of artistic creativity.